Electrochemical properties of graphite/nylon electrodes additively manufactured by laser powder bed fusion - Pastushok Olga; Kivijärvi Lauri; Laakso Ekaterina; Haukka Matti; Piili Heidi; Repo Eveliina (Elsevier Ltd, 2025)
Nowadays, additive manufacturing, known as 3D printing, is vigorously employed at various enterprises due to the ability of industrial series production and customization in conjunction with geometry freedom. While, material design and fabrication of composite materials, meeting the desired architecture and properties, is another promising application of additive manufacturing. For instance, additive manufacturing of the material exhibiting electrochemical properties is beneficial for the development of freestanding electrodes that might be used in electrochemical energy storage systems. Herein, the graphite/nylon composite with a high carbon ratio of 30 wt% was produced by laser powder bed fusion to promote the development of the additive manufacturing of electrochemical energy storage devices. The material characterization of the additively manufactured graphite/nylon electrode demonstrates the porous structure with uniform distribution of the compounds, and the absence of chemical interactions between them during laser powder bed fusion. The electrochemical properties of the composite were investigated in acidic, neutral, and alkaline electrolytes. The tested additively manufactured electrodes demonstrate a capacitive behaviour and a stable electrochemical performance with average capacitance retention of 95%. The findings open new frontiers for the development and improvement of the production of electrochemically active materials by additive manufacturing with consideration to design freedom and customization.